Gravity wave propagation through a large semidiurnal tide and instabilities in the mesosphere and lower thermosphere during the winter 2003 MaCWAVE rocket campaign - Williams, B. P.; Fritts, D. C.; She, C. Y.; Goldberg, R. A. (HAL CCSD, 2006)
International audience The winter MaCWAVE (Mountain and convective waves ascending vertically) rocket campaign took place in January 2003 at Esrange, Sweden and the ALOMAR observatory in Andenes, Norway. The campaign combined balloon, lidar, radar, and rocket measurements to produce full temperature and wind profiles from the ground to 105 km. This paper will investigate gravity wave propagation in the mesosphere and lower thermosphere using data from the Weber sodium lidar on 28?29 January 2003. A very large semidiurnal tide was present in the zonal wind above 80 km that grew to a 90 m/s amplitude at 100 km. The superposition of smaller-scale gravity waves and the tide caused small regions of possible convective or shear instabilities to form along the downward progressing phase fronts of the tide. The gravity waves had periods ranging from the Nyquist period of 30 min up to 4 h, vertical wavelengths ranging from 7 km to more than 20 km, and the frequency spectra had the expected ?5/3 slope. The dominant gravity waves had long vertical wavelengths and experienced rapid downward phase progression. The gravity wave variance grew exponentially with height up from 86 to 94 km, consistent with the measured scale height, suggesting that the waves were not dissipated strongly by the tidal gradients and resulting unstable regions in this altitude range.